The ethical concerns of bioanalytical chemistry: the case of forensic science - Shogar, Ibrahim Adam Ahmed; Abd Hamid, Shafida; Mohd Yusof, Nazri (2018)
Due to its pragmatic nature, bioanalytical science, a sub-discipline of analytical chemistry, is increasingly becoming a central point to address the practical needs of modern community life. It seems to be very promising and potential to play a major role in many sectors of industrial, environmental and medical applications. It nevertheless, encompasses various forms of analytical chemistry, such as: (i) bioanalysis for medical and clinical purposes, especially in the pharmaceutical industry; (ii) quality assurance purposes in food industry and products; (iii) bioanalysis for environmental and ecosystem; and (iv) bioanalysis for forensic purposes. The practical part of all these sciences depends on bioanalytical chemistry, which is based on techniques and technologies that are characterized by accuracy, preciseness and honesty. To harness potentials of the newly growing science of bioanalysis, the analytical chemists need to address, not only matters of accuracy and preciseness of measurement methods and techniques, but also the ethical implications of bioanalysis. In fact, the ethical concerns are arising alongside with the various techniques adopted, application methods, fraudulent cases, negligence, as well as other problems that may jeopardize the integrity of bioanalytical science. This paper focuses, especially, on the ethical aspects of forensic science which depends solely on bioanalytical chemistry. Forensic science is mainly concerned with using results of bioanalysis for legal purposes, to draw evidences for conviction. Although there is a considerable literature on forensic science, however, the ethical dimension of this science needs further investigation, especially based on technical study of bioanalytical chemistry, as aimed by this paper. The paper, firstly, outlines briefly the basic forms of bioanalytical chemistry, as summarized above, and their technical methods of analysis; secondly, the paper investigates the ethical implications of forensic science. The method adopted will be theoretical, analytic and critical in nature.